2021
DOI: 10.1038/s41598-021-94795-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lighting illuminance and colour temperature on mental workload in an office setting

Abstract: The mental workload of subjects was tested under different lighting conditions, with colour temperatures ranging from 3000 to 6500 K and illuminance ranging from 300 to 1000 lx. We used both psychological and physiological responses for evaluation. The former was based on NASA Task Load Index (NASA-TLX, NASA), and the latter was based on the electroencephalogram (EEG) P3b analysis of event-related potentials using the “oddball” paradigm experimental task. The results show that as illuminance increases, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This aligns with earlier research that illuminance variations do not significantly impact productivity over short durations (Fu et al, 2023a;Yu and Akita, 2023). However, for 60-min reading duration, a moderate increase in illuminance is suggested to achieve optimal lighting conditions (Bao et al, 2021). This finding is consistent with previous studies, including that of Bania, which found that 750 lux to be more suitable than 500 lux (Baniya et al, 2015).…”
Section: Suggestions For Lighting Environments For Different Reading ...supporting
confidence: 91%
“…This aligns with earlier research that illuminance variations do not significantly impact productivity over short durations (Fu et al, 2023a;Yu and Akita, 2023). However, for 60-min reading duration, a moderate increase in illuminance is suggested to achieve optimal lighting conditions (Bao et al, 2021). This finding is consistent with previous studies, including that of Bania, which found that 750 lux to be more suitable than 500 lux (Baniya et al, 2015).…”
Section: Suggestions For Lighting Environments For Different Reading ...supporting
confidence: 91%
“…In 2021, Bao et al conducted a study to investigate the effects of illuminance and colour temperature on mental workload. They reported that the effect of color temperature and illuminance on participants' mental workload was not clear [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation may be that the dynamics of light, as well as participants' prior mental state were both involved in the process of activating the arousal level, which had been studied in earlier research. 27,57 However, this hypothesis is inconsistent with the results of the study by Kompier et al, 58 where no significant effects of light transition were found on PVT performance. Therefore, future studies should carefully control fatigue induction and CCT manipulation to explore whether mental antecedent condition and the dynamics of light potentially regulate acute alerting effects.…”
Section: Alertnessmentioning
confidence: 73%